Analisis Vrio dan Swot Sebagai Dasar Perumusan Strategi Pengembangan Teknologi Informasi pada CV. Situsindo Prima (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to formulate an information technology development strategy for CV. Situsindo Prima using the VRIO (Value, Rarity, Imitability, Organization) and SWOT (Strengths, Weaknesses, Opportunities, Threats) approaches. CV. Situsindo Prima is a company engaged in Software Development and IT Consulting, focusing on providing technological solutions for both public and private sectors in Purwokerto, Indonesia. The research employs a qualitative descriptive approach by utilizing secondary data obtained from the company profile, literature reviews, and previous studies relevant to strategic information systems management. The results indicate that the company possesses several competitive advantages derived from its competent human resources, strong project reputation, and well-established relationships with public institutions. The VRIO analysis reveals that these resources have significant strategic value and potential for sustainable competitive advantage if supported by an effective organizational system. The SWOT analysis further identifies that internal strengths can be leveraged to capture external opportunities, such as the increasing demand for digital transformation and government support for technological innovation. The formulated strategies include developing a knowledge management system, implementing Service Level Agreements (SLA) for after-sales services, innovating products based on cloud computing and Internet of Things (IoT), and enhancing human resource capabilities through training and certification programs. In conclusion, this research successfully achieved its objectives by producing a comprehensive and applicable IT development strategy for CV. Situsindo Prima. The findings are expected to serve as a reference for strategic planning and strengthening competitive advantage within the digital transformation era.